2013
DOI: 10.1021/jo302572s
|View full text |Cite
|
Sign up to set email alerts
|

Nitroalkenes as Carbonyl Surrogates in Arylmethyl-homoallylic Alcohol Forming One-Pot Allylation Reactions in Water

Abstract: A simple and practical approach has been developed for conducting direct, homoallylic alcohol forming allylation reactions of nitroalkenes in water. Employing the new method, various arylmethyl-homoallylic alcohols can be produced from the corresponding, readily prepared β-nitrostyrenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These indicated that the side product 5a was formed through deacylation/cyclation of acylhydrazone 12a in the presence of in situ formed tin salts. Thus, a possible mechanism was proposed as in Scheme on the basis of our experiment results and the literature . Acylhydrazones 12 were formed from condensation of 2-formylbenzoic acids 1 and hydrazides 2 , and nucleophilic addition of in situ formed organotin reagents 14 to acylhydrazones 12 produced intermediates 16 , which were then cyclized to afford products 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These indicated that the side product 5a was formed through deacylation/cyclation of acylhydrazone 12a in the presence of in situ formed tin salts. Thus, a possible mechanism was proposed as in Scheme on the basis of our experiment results and the literature . Acylhydrazones 12 were formed from condensation of 2-formylbenzoic acids 1 and hydrazides 2 , and nucleophilic addition of in situ formed organotin reagents 14 to acylhydrazones 12 produced intermediates 16 , which were then cyclized to afford products 4 .…”
Section: Resultsmentioning
confidence: 99%
“…This method not only kept the advantages of organotin reagents, but also avoided the use of toxic allylstannanes. Afterward, tin powder-promoted organic reactions have been studied widely by organic chemists . These advantages encouraged us to investigate the application of tin powder-promoted reactions in the construction of nitrogen-containing heterocycles.…”
Section: Introductionmentioning
confidence: 90%
“…Afterwards, more and more attention has been paid to tin powder‐promoted reactions. Especially, some reactions could be carried out in the presence of water or in pure water . This technique avoided the use of toxic stannanes while retaining their merits such as moisture stability, tolerance to functional groups and high selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, allylations mediated by metallic tin were investigated in the presence of water or just using water as solvent, but most studies focused on allylation of aldehydes. [31,[51][52][53][54][55] Some other substrates such as nitroalkenes, [11] enol ethers [56] and aldoximes [57] were also allylated using allylic bromide and metallic tin in water to give homoallylic alcohols.…”
Section: Introductionmentioning
confidence: 99%